WIPI1 promotes fission of endosomal transport carriers and formation of autophagosomes through distinct mechanisms. Issue 11 (2nd November 2021) - De Leo, Maria Giovanna; Berger, Philipp; Mayer, Andreas
ABSTRACT: Autophagosome formation requires PROPPIN/WIPI proteins and monophosphorylated phosphoinositides, such as phosphatidylinositol-3-phosphate (PtdIns3P) or PtdIns5P. This process occurs in association with mammalian endosomes, where the PROPPIN WIPI1 has additional, undefined roles in vesicular traffic. To explore whether these functions are interconnected, we dissected routes and subreactions of endosomal trafficking requiring WIPI1. WIPI1 specifically acts in the formation and fission of tubulo-vesicular endosomal transport carriers. This activity supports the PtdIns(3, 5)P2 -dependent transport of endosomal cargo toward the plasma membrane, Golgi, and lysosomes, suggesting a general role of WIPI1 in endosomal protein exit. Three features differentiate the endosomal and macroautophagic/autophagic activities of WIPI1: phosphoinositide binding site II, the requirement for PtdIns(3, 5)P2, and bilayer deformation through a conserved amphipathic α-helix. Their inactivation preserves autophagy but leads to a strong enlargement of endosomes, which accumulate micrometer-long endosomal membrane tubules carrying cargo proteins. WIPI1 thus supports autophagy and protein exit from endosomes by different modes of action. We propose that the type of phosphoinositides occupying its two lipid binding sites, the most unusual feature of PROPPIN/WIPI family proteins, switches between these effector functions. Abbreviations: EGF: epidermal growth factorEGFR: epidermal growth factor receptorKD: knockdownKO: knockoutPtdIns3P: phosphatidylinositol-3-phosphatePtdIns5P: phosphatidylinositol-5-phosphatePtdIns(3, 5)P2 : phosphatidylinositol-3, 5-bisphosphateTF: transferrinTFRC: transferrin receptorWT: wildtype